Encapsulation of benznidazole in nanostructured lipid carriers and increased trypanocidal activity in a resistant Trypanosoma cruzi strain - Flávia Lidiane Oliveira da Silva; Maria Betânia de Freitas Marques; Maria Irene Yoshida; Wagner da Nova Mussel; João Vinícios Wirbitzki da Silveira; Poliana Ribeiro Barroso; Kelly Cristina Kato; Helen Rodrigues Martins; Guilherme Carneiro (Universidade de São Paulo, 2023)
Abstract Chagas disease is a neglected parasitic disease caused by Trypanosoma cruzi, whose treatment has remained unsatisfactory for over 50 years, given that it is limited to two drugs. Benznidazole (BZN) is an efficient antichagasic drug used as the first choice, although its poor water-solubility, irregular oral absorption, low efficacy in the chronic phase, and various associated adverse effects are limiting factors for treatment. Incorporating drugs with such characteristics into nanostructured lipid carriers (NLC) is a promising alternative to overcome these limiting obstacles, enhancing drug efficacy and bioavailability while reducing toxicity. Therefore, this study proposed NLC-BZN formulations in different compositions prepared by hot-melt homogenization followed by ultrasound, and the optimized formulation was characterized by FTIR, DRX, DSC, and thermogravimetry. Biological activities included in vitro membrane toxicity (red blood cells), fibroblast cell cytotoxicity, and trypanocidal activity against epimastigotes of the Colombian strain of T. cruzi. The optimized NLC-BZN had a small size (110 nm), negative zeta potential (-18.0 mV), and high encapsulation (1.64% of drug loading), as shown by infrared spectroscopy, X-ray diffraction, and thermal analysis. The NLC-BZN also promoted lower in vitro membrane toxicity (<3% hemolysis), and 50% cytotoxic concentration (CC50) for NLC-BZN in L929 fibroblast cells (110.7 µg/mL) was twice the value as the free BZN (51.3 µg/mL). Our findings showed that the NLC-BZN had higher trypanocidal activity than free BZN against the epimastigotes of the resistant Colombian strain, and this novel NLC-BZN formulation proved to be a promising tool in treating Chagas disease and considered suitable for oral and parenteral administration.